A Nodular Calcification of the Alar Ligament Simulating a Fracture in the Craniovertebral Junction - Sim, K.-B.; Park, J.K. (American Journal of Neuroradiology, 2006)
SUMMARY: We report a case of an incidental nodular calcification of the alar ligament simulating a fracture in the craniovertebral junction of a previously healthy 24-year-old man. Three-dimensional CT and MR imaging revealed a 7.2 × 7.6 × 4.0 mm nodular calcification in the right alar ligament with normal adjacent bony structures. Serial cervical dynamic radiographs and open-mouth views showed that the cervical spine was stable without any change in the calcification.